Biodiversity outcomes of nature-based solutions for climate change adaptation: Characterising the evidence base - Key, Isabel B.; Smith, Alison C.; Turner, Beth; Chausson, Alexandre; Girardin, Cécile A. J.; Macgillivray, Megan; Seddon, Nathalie (Frontiers in Environmental Science, 2022)
Nature-based solutions (NbS) are increasingly recognised for their potential to address both the climate and biodiversity crises. Both these outcomes rely on the capacity of NbS to support and enhance the health of an ecosystem: its biodiversity, the condition of its abiotic and biotic elements, and its capacity to function normally despite environmental change. However, while understanding of ecosystem health outcomes of NbS for climate change mitigation has developed in recent years, the outcomes of those implemented for adaptation remain poorly understood. To address this, we systematically reviewed the outcomes of 109 nature-based interventions for climate change adaptation using 33 indicators of ecosystem health across eight broad categories (e.g. diversity, biomass, ecosystem composition). We showed that 88% of interventions with reported positive outcomes for climate change adaptation also reported benefits for ecosystem health. We also showed that interventions were associated with a 67% average increase in species richness. All eight studies that reported benefits for both climate change mitigation and adaptation also supported ecosystem health, leading to a “triple win”. However, there were also trade-offs, mainly for forest management and creation of novel ecosystems such as monoculture plantations of non-native species. Our review highlights two key limitations in our understanding of the outcomes of NbS for ecosystem health. First, a limited selection of metrics are used and these rarely include key aspects such as functional diversity and habitat connectivity. Second, taxonomic coverage is limited: 50% of interventions only had evidence for effects on plants, and 57% of outcomes did not distinguish between native and non-native species. We make suggestions of how to improve assessments of the ecosystem health outcomes of NbS, as well as policy recommendations to enable the upscaling of NbS that support healthy and resilient ecosystems, and are effective in addressing both climate and biodiversity goals.